Social Insurance and Redistribution - Robin Boadway; Manuel Leite-Monteiro; Maurice Marchand; Pierre Pestieau (Queen's University, Department of Economics, 2002)
This paper studies optimal linear income taxation and redistributive social insurance when the former has the traditional labor distortion and the latter generates both ex ante and ex post moral hazard. Private insurance is available and individuals differ in labor productivity and in loss probability. We show that government intervention in insurance markets is welfare-improving, and social insurance is generally desirable when there is a negative correlation between labor productivity and loss probability.
Keywords: H23; H51; 330; Social Insurance; Moral Hazard; Redistribution; Einkommensteuer; Sozialversicherung; Umverteilung; Theorie